Small Bowel Morphology in Chronic Infantile Diarrhoe - Pitono Soeparto; I Wayan Giri (Indonesian Pediatric Society, 1982)
Before the introduction of in vivo intestinal biopsy techniques, relatively little was known about the morphology of human intestinal mucosa under normal condition, and still less about its pathological states.The first intestinal biopses were carried out with a modification of the rigid gastnic biopsy tube (Shiner, 1956) and it was only after the introduction of the much more flexible biopsy capsule (Crosby and Kugler, 1951) that the technique of intestinal biopsy became extensively used throughout the world (Greene et al., 1974; Townley and Bernes, 1973). In 1962, Readand his colleagues produced a modification of Crosby's capsule, and a paediatric ver on of the modification is Received 14th Mei 19!0.now widely used fur small intestinal biopsy lin children (Marketed as WatsonCapsule).